Endoscopic papillectomy or pancreaticoduodenectomy for ampullary lesions: a single center retrospective cohort study - Seyfried, Steffen; Kähler, Georg; Belle, Sebastian; Hirsch, Daniela; Reißfelder, Christoph; Rahbari, Nuh Nabi; Hardt, Julia (Scandinavian journal of gastroenterology, 2022)
Background This study aimed to compare post-operative morbidity, mortality, and completeness of resection following endoscopic vs. radical surgical resection for ampullary lesions.Methods A retrospective analysis of the prospectively collected data from a surgical database for patients with ampullary lesions at our institution was performed. All consecutive patients undergoing endoscopic papillectomy (EP) or pancreaticoduodenectomy (PD) for ampullary lesions between 2007 and 2021 were eligible for this analysis.Results A total of 85 patients were included of whom 42 underwent EP whereas 43 received a PD. The resected lesion was a tubulovillous adenoma in 26 patients (61.9%) in the EP cohort, and 37 patients (86.0%) in the PD cohort had adenocarcinomas. The completeness of resection was equal in both cohorts. Significantly more patients of the PD cohort had to undergo reinterventions. After a mean follow up of 36 months (EP) vs. 16 months (PD), the rate of tumor recurrence did not differ between both groups.Conclusion Equivalently high completeness of resection rates and correspondingly low recurrence rates can be achieved after EP and PD. Our results regarding residual tumor and recurrence rates show that even large tumors can be resected endoscopically with high primary success and completeness of resection rates.
Gesehen am 25.07.2023